EVALUASI KONDISI JALAN SALATIGA-SRUWEN KM. SMG 57+050 - KM. SMG 59+050 TERHADAP KATEGORI RESIKO TERJADINYA KECELAKAAN - Setyowati, Sutari; Setyawan, Ary; Djumari, Djumari (Matriks Teknik Sipil, 2014)
Traffic accidents is an event where the collision of vehicles moving on the road that led to humans or animals can be injured even to death. Salatiga-Sruwen STA 57+050 to STA 59+050 road is a primary arterial road that connects between Surakarta and Semarang. The road has hightraffic levels and thus potentially cause accidents on the road hence the need for an analysis of the risk category of traffic accidents. Evaluation ofroad conditions Salatiga-Sruwen over the risk of accidents need to be conducted to identify high risk situations or potential accidents that usuallycaused by human, road conditions, vehicle, weather, environment and unobstructed view. So the situation can be addressed to reduce the possibilityof accidents.This study aims to determine the category of the risk accidents level. this evaluation applies D checklist: Road Safety Audit operational road levelthat has been issued by the department of public works. Analysis focused on the answer yes or no and identified the other supporting infrastructurethat have not been technically meets the standards and requirements. Primary data obtained from the field observations and secondary data wereused in 2013 accidents that obtained from tengaran police sector and as built drawing.From the research in Salatiga-Sruwen road KM.SMG 57+050-KM.SMG 59+050 results the road conditions is good as they meet the technicalrequirements of airworthiness to provide safety for its users and administrative requirements that provide legal certainty for providers and users ofthe road that the road can be operated for the public. Salatiga-Sruwen road KM.SMG 57+050-KM.SMG 59+050 has a value risk category11 with a harmless risk and risk value 160 is quite dangerous with the risk category that should be repaired immediately to minimize the potentialfor accidents